The distinct genetic pattern of ALS in Turkey and novel mutations - Özoğuz, Aslıhan; Uyan, Özgün; Birdal, Güneş; Iskender, Ceren; Kartal, Ece; Lahut, Suna; Ömür, Özgür; Agim, Zeynep Sena; Eken, Aslı Gündoğdu; Sen, Nesli Ece; Kavak, Pınar; Saygı, Ceren; et al. (Neurobiology of aging, 2015)
The frequency of amyotrophic lateral sclerosis (ALS) mutations has been extensively investigated in several populations; however, a systematic analysis in Turkish cases has not been reported so far. In this study, we screened 477 ALS patients for mutations, including 116 familial ALS patients from 82 families and 361 sporadic ALS (sALS) cases. Patients were genotyped for C9orf72 (18.3%), SOD1 (12.2%), FUS (5%), TARDBP (3.7%), and UBQLN2 (2.4%) gene mutations, which together account for approximately 40% of familial ALS in Turkey. No SOD1 mutations were detected in sALS patients; however, C9orf72 (3.1%) and UBQLN2 (0.6%) explained 3.7% of sALS in the population. Exome sequencing revealed mutations in OPTN, SPG11, DJ1, PLEKHG5, SYNE1, TRPM7, and SQSTM1 genes, many of them novel. The spectrum of mutations reflect both the distinct genetic background and the heterogeneous nature of the Turkish ALS population.